THE INTERRELATION BETWEEN FORENSIC MEDICINE AND PATHOPHYSIOLOGY - Miraxmedova Nargiz Rizoyevna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract Forensic medicine and pathophysiology are closely interconnected disciplines that together provide deep insights into the mechanisms of injury, disease, and death. Pathophysiology,  which  studies  functional  changes  in  the  body  resulting  from pathological  processes,  forms  the  scientific  basis  for  interpreting  many  findings  in forensic  examinations.  This  paper  explores  how  understanding  pathophysiological mechanisms enhances forensic diagnostics, particularly in establishing the cause and mechanism of death, injury assessment, and forensic interpretation of disease-related deaths.